PRENATAL PREDICTORS OF VITAMIN D DEFICIENCY IN NEONATES - Dr. Asif Ashraf; Dr. Sana (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Vitamin D plays a vital role in fetal skeletal development and immune regulation. During pregnancy, the fetus is entirely dependent on maternal 25(OH)D levels, which are influenced by sun exposure, dietary intake, and maternal health. Deficiency in vitamin D has been associated with adverse outcomes in both mother and neonate.Objective: To assess the prevalence of vitamin D deficiency in pregnant women and its correlation with neonatal cord blood vitamin D levels, as well as evaluate associated maternal factors such as parity, BMI, and sun exposure.Methods: This prospective observational study included 100 pregnant women (20–40 years) with singleton term pregnancies, conducted at Government Medical College, Srinagar. Maternal and cord blood samples were analyzed for 25(OH)D levels using ELISA. Vitamin D status was categorized as deficient (50 nmol/L). Associations were examined using Chi-square and Pearson correlation tests.Results: Vitamin D deficiency was observed in 56% of mothers and 58% of neonates. A significant correlation existed between maternal and neonatal vitamin D levels (p = 0.001). Deficiency was highest in underweight (78.6%), nulliparous (83.3%), and women with no sun exposure (71.4%). Statistically significant associations were noted for parity (p = 0.047), BMI (p = 0.047), and sun exposure (p = 0.0002), but not for maternal age (p = 0.5241).Conclusion: Maternal vitamin D status significantly influences neonatal levels. Routine antenatal screening, supplementation, and promoting sun exposure should be prioritized, especially in high-risk subgroups, to prevent deficiency-related complications.